Ardmore Wildcats majorettes, 1959. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 11-15-59.
Ardmore Wildcats majorettes, 1959. The girls are, from top to bottom starting at the left: Judy Sweat, Marlene Pettit, Connie Moore and Janice Moore; top to bottom on the right, Connie Stegall, Carla Humphries, Nancy Davis, and Liza Frazier.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth